Application of interferon in complex therapy of respiratory disorders in prematurely newborns - A. G. Yunusov; P. G. Zarifova; S. M. Negmatullaeva; N. N. Niyazova; T. N. Kholova (Лечащий Врач)
Clinical and immunological efficiency of use of recombinant alpha-2b interferon preparation as a component of complex therapy of respiratory disorders in prematurely newborns was studied. It was shown that, in prevention and treatment of intrauterine infections of the fetus and the newborn, except for etiotropic, immune-correcting therapy is also very important. Inclusion of recombinant alpha-2b interferon preparation in the complex therapy contributes to improvement of the course, and reduction of duration of the disease.